2020
DOI: 10.1002/ange.201915084
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalysed Radical Polymerisation by Living Bacteria

Abstract: The ability to harness cellular redox processes for abiotic synthesis might allow the preparation of engineered hybrid living systems. Towards this goal we describe a new bacteria‐mediated iron‐catalysed reversible deactivation radical polymerisation (RDRP), with a range of metal‐chelating agents and monomers that can be used under ambient conditions with a bacterial redox initiation step to generate polymers. Cupriavidus metallidurans, Escherichia coli, and Clostridium sporogenes species were chosen for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Minimal polymerisation was observed in the absence of live cells, indicating the importance of cellular metabolism to the catalytic cycle to regenerate active Fe(II). 17 It is noteworthy that polymerisation was also observed with the Gram-positive anaerobe Clostridium sporogenes, however only 34% conversion was achieved in comparison to 61% and 78% for C. metallidurans and E. coli, respectively. This was hypothesised to be due to C. sporogenes being less efficient at reducing Fe(III) than Gram-negative strains.…”
Section: Microbe Mediated Polymerisationmentioning
confidence: 96%
See 2 more Smart Citations
“…Minimal polymerisation was observed in the absence of live cells, indicating the importance of cellular metabolism to the catalytic cycle to regenerate active Fe(II). 17 It is noteworthy that polymerisation was also observed with the Gram-positive anaerobe Clostridium sporogenes, however only 34% conversion was achieved in comparison to 61% and 78% for C. metallidurans and E. coli, respectively. This was hypothesised to be due to C. sporogenes being less efficient at reducing Fe(III) than Gram-negative strains.…”
Section: Microbe Mediated Polymerisationmentioning
confidence: 96%
“…16 Radical polymerisation has also been demonstrated using the metal-reducing Gram-negative bacterium Cupriavidus metallidurans and the model laboratory bacterium Escherichia coli. 17 Native membrane reductases in both organisms were able to reduce Fe(III) to Fe(II) to activate a series of radical initiators for ATRP. Minimal polymerisation was observed in the absence of live cells, indicating the importance of cellular metabolism to the catalytic cycle to regenerate active Fe(II).…”
Section: Microbe Mediated Polymerisationmentioning
confidence: 99%
See 1 more Smart Citation
“…During the polymerization of pyrrole they observed cancer cell death, which provides another application of this pyrrole polymerization mechanism as ‘reverse pro drug’ systems, meaning that cytotoxic pyrrole after cell death tends to polymerize, which yields biocompatible conducting polymer–polypyrrole [ 101 ] that is black-colored and, therefore, can also be used as optical indicator of dead cells. Following this, it was reported that implementing FeCl 3 compound with metal reduction-capable bacteria: Cupriavidus metallidurans , Escherichia coli and Clostridium sporogenes , could initiate atom transfer radical polymerization (ATRP) of various monomers (poly (ethylene glycol methyl ether methacrylate); hydroxyethyl methacrylate; N-hydroxyethyl acrylamide; 2-acrylamido-2-methyl-1-propanesulfonic sodium; 2-(methacryloyloxy) ethyl dimethyl-(3- sulfopropyl) ammonium hydroxide [ 144 ]. Researchers suggested interesting approach for designing cell-assisted polymerization.…”
Section: Modifications Of Microorganisms To Improve Mfcs Performanmentioning
confidence: 99%
“…One strategy toward achieving this in vivo integration of bioelectronic interfaces is the use of the cell machinery to engineer this interface. For instance, extracellular electron transfer enzymes on the cell membrane can initiate the polymerization of different monomers catalyzed by iron reduction in bacteria (Bennett et al, 2020). This method can also be applied to conductive polymers, where a polypyrrole layer was grown in cancer cell lines due to their higher metabolic rates to induce their death, acting as a reverse pro‐drug (Sherman et al, 2019).…”
Section: Wireless Nanobioelectronic Toolsmentioning
confidence: 99%